One-pot fabrication of superhydrophobic and flame-retardant coatings on cotton fabrics via sol-gel reaction - Lin, Dongmei; Zeng, Xingrong; Li, Hongqiang; Lai, Xuejun; Wu, Tongyi (Journal of colloid and interface science, 2019)
[Display omitted] Waterproof and flame-retardant fabrics are widely utilized in many fields, such as automotive interiors, indoor decorations, outdoor clothing and tents. Herein, a facile one-pot sol-gel approach was developed to construct superhydrophobic and flame-retardant (SFR) coatings on cotton fabrics. The cotton fabric was activated by O2 plasma and then immersed into the ethanol suspension containing tetraethoxysilane (TEOS), hydroxyl-terminated polydimethylsiloxane (HPDMS) and ammonium polyphosphate (APP). The hydrogen bonding interaction between APP and cellulose motivated the APP to attach to the cotton fibers during the initial stirring process. After the addition of ammonia, the in situ sol-gel reaction of TEOS and HPDMS was initiated to generate polydimethylsiloxane-silica hybrid (PDMS-silica). The micro-nano structured composite coating on cotton fabric was successfully fabricated by the PDMS-silica and APP. The SFR cotton fabric showed outstanding durability and self-cleaning ability with a water contact angle (WCA) above 160°. When exposed to fire, the SFR cotton fabric quickly charred to extinguish the fire by generating a dense intumescent char layer under the physical barrier effect of PDMS-silica and the intumescent flame-retardant effect of APP. This one-pot approach for fabricating SFR cotton fabric is simple, cost-effective and timesaving, demonstrating significant advantages in practical production.